Design of Sustainable Transportation Networks - Wendelin Gross; Christian Butz (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
The stakeholders of companies have increased their focus on sustainability of the business activities in the course of a societal paradigm shift towards intergenerational equity. The triple bottom line of economical, ecological, and social sustainability has become a standard model for the overall purpose of businesses. Therefore, companies in retail and manufacturing sectors tend to improve their carbon footprint and reduce emissions of Greenhouse Gas (GHG). The scope of this work is the strategic design of logistics network according to sustainability criteria by means of mathematical optimization methods. GHG emissions of road transportation for the delivery of goods to manufacturing sites or the point of sale are taken into account. The paper applies a facility location model to identify ecologically and economically efficient network configuration for given demands, road infrastructure, and equipment. The proposed research design provides insight into the trade-off between cost efficient and emission efficient network design, and presents metrics that can be applied to a facility location problem in order to pursue the ecological sustainability target. The application in two scenarios show the viability for real-world sized data sets.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650